Factors influencing the functionality of medicines and therapeutic committees in public health facilities in Uganda: A longitudinal assessment - Benard Nsubuga; Anthony Ddamba; Harriet Akello; David Arinaitwe; Phillip Ampaire; Moses Kamabare (PLoS ONE, 2026)
World health organization estimates that of all medicines used globally, about 50% are used irrationally. This is mostly attributed to overuse of antibiotics and indiscriminate use of injectables, among other things. Globally, medicines and therapeutic committees (MTCs) play a significant role in combating inappropriate medicines use problems. This study explored the extent of the functionality of MTCs in health facilities in Uganda and the associated factors. This was a longitudinal assessment that utilised a semistructured questionnaire that was administered through face-to-face interviews. Panel data analysis techniques were used to compare results between the two waves. This study utilised the ordered logistic regression model and random effects techniques to determine the factors influencing the functionality of MTCs. Overall, the percentage of health facilities with a functional MTC significantly increased from 8.3% (22/264) in wave one to 20.8% (55/265) in wave two (p-value = 0.000). The percentage of MTCs that are partially functioning increased from 15.2% (40/264) in wave one to 29.1% (77/265) in wave two. The percentage of HFs with MTC structures increased from 2.6% to 42.6% in wave two. Health facilities without an MTC significantly reduced from 72% (190/264) in wave one to 7.6% (20/265) in wave two (p-value = 0.0000). The median number of MTC members significantly increased from 13 in wave one to 15 members in wave two (p-value = 0.0112). Level of care, availability of guidelines, availability of subcommittees, and MTC members being active were significantly associated with the performance of MTCs (p-value<0.05). The study established a significant improvement in the functionality of MTCs in health facilities attributed to interventions from national medical stores, Uganda’s ministry of health and implementing partners. The study, however, observed little improvement in the full functionality of MTC subcommittees. Continuous medical education interventions should be strengthened at all levels of care.